Exploring polymorphism of benzene and naphthalene with free energy based enhanced molecular dynamics. Issue 4 (3rd August 2016) - Schneider, Elia; Vogt, Leslie; Tuckerman, Mark E.
Abstract : The crystal structures of benzene and naphthalene are successfully predicted for atmospheric and high‐pressure conditions. Using enhanced molecular dynamics based sampling, we find that mixed structures, which typically cannot be discovered by standard crystal structure prediction methods, are prevalent in the solid forms of these compounds at high pressure. Abstract : Prediction and exploration of possible polymorphism in organic crystal compounds are of great importance for industries ranging from organic electronics to pharmaceuticals to high‐energy materials. Here we apply our crystal structure prediction procedure and the enhanced molecular dynamics based sampling approach called the Crystal‐Adiabatic Free Energy Dynamics (Crystal‐AFED) method to benzene and naphthalene. Crystal‐AFED allows the free energy landscape of structures to be explored efficiently at any desired temperature and pressure. For each system, we successfully predict the most stable crystal structures at atmospheric pressure and explore the relative Gibbs free energies of predicted polymorphs at high pressures. Using Crystal‐AFED sampling, we find that mixed structures, which typically cannot be discovered by standard crystal structure prediction methods, are prevalent in the solid forms of these compounds at high pressure.